Jalan Baru Memaknai Hubungan Filsafat dan Agama dalam Pemikiran Al-Kindidan Sutan Takdir Alisyahbana - Pratama, Alexander Bayu Putra; Prasetya, Nirwan; Mulyatno, Carolus Borromeus (Fakultas Teologi, Universitas Sanata Dharma, 2024)
This qualitative research aims to explore the ideas of Al-Kindi and Sutan Takdir Alisyahbana on the relationship between philosophy and religion. Philosophy and religion are often seen as opposites. For these two figures, philosophy and religion have a close relationship and cannot be separated from life. The method used to collect data in this research is literature study. The results of this research include three points. First, Al-Kindi's ideas about the relationship between philosophy and religion in the framework of Islamic thought. Second, Sutan Takdir Alisyahbana's ideas about the importance of philosophy in developing rationality and adapting to Western culture, while still maintaining religious values. Third, a new understanding of the relationship between philosophy and religion. They need to be opposed but can complement each other in the search for truth and a deep understanding of religious teachings.AbstrakPenelitian kualitatif ini bertujuan untuk mengeksplorasi gagasan Al-Kindi dan Sutan Takdir Alisyahbana tentang hubungan filsafat dan agama. Filsafat dan agama sering dianggap sebagai dua hal yang bertentangan. Bagi kedua tokoh ini, filsafat dan agama memiliki hubungan yang erat dan tidak bisa dipisahkan dari kehidupan. Metode yang digunakan untuk mengumpulkan data dalam penelitian ini adalah studi pustaka. Hasil dari penelitian ini meliputi tiga pokok. Pertama, gagasan Al-Kindi tentang hubungan filsafat dan agama dalam kerangka pemikiran Islam. Kedua, gagasan Sutan Takdir Alisyahbana tentang pentingnya filsafat dalam mengembangkan rasionalitas dan beradaptasi dengan budaya Barat, sambil tetap mempertahankan nilai-nilai religius. Ketiga, pemahaman baru tentang hubungan filsafat dan agama, keduanya tidak harus dipertentangkan melainkan dapat saling melengkapi dalam pencarian kebenaran dan pemahaman mendalam terhadap ajaran-ajaran agama.